Etabolism in compensatory growth . III. The urea, glucose and C02 entry rates in animal undergoing compensatory growth - Mahyudin, Pram; Teleni, E (Indonesian Animal Sciences Society, 1996)
Glucose (GER), Urea (UER) and C02 (C02 ER) entry rates were studied at four points in the growth curve viz: before feed restriction (PI) after 8 weeks of feed restriction (P2), after 3 weeks (P3) and 15 weeks (P4) following resumption ofad libitum feeding. Sixteen Merino wethers were used and offerred pelleted lucerne (Medicago sativa) ad libitum for 3 weeks; then they were divided into 2 groups of eight. Group I continued to be fed ad libitum and Group 11 was fed pelleted lucerne at half maintenance level for 8 weeks and then fed ad libitum until the end of experiment. During feed restriction (P2), UER, urinary urea and urea transferred from the blood to the gut were 74% lower in group II than those in group I due to the reduction of N intake . At P2 GER and C02ER were also lower (53% and 56%, respectively) because of the reduction of available glucose precursor and metabolic rate. Similarly AV concentration difference of glucose, glucose taken up by the hind-limb muscle and the percentage of glucose taken up by muscle that was oxidised were reduced by 52%, 86% and 48%, respectively . When animals resumed ad libitum feeding, the components of urea entry rate (except plasma urea concentration), GER and C02ER were markedly increased indicating A switch to the anabolic mode, followed by increased glucose taken up and oxidised by the hind-limb muscle . The significance of glucose in muscle metabolism during compensatory growth was shown in the dramatic increase in the actual rate of glucose oxidation per unit muscle weight . It appears that the priority of usage of glucose taken up by muscle during compensatory growth is for oxidation to both C02 and lactate. Â Key words: Glucose entry rate, C02 entry rate, plasma urea